Effects of ethanolic extract and cernumidine compound obtained from Solanum cernuum's Vell. leaves on benign prostatic hyperplasia - Mariza Abreu Miranda; Claudia Sares; Augusto Faria Andrade; Kleiton Silva Borges; James Dewey McChesney; Jairo Kenupp Bastos; Rodolfo Borges dos Reis (Institue of Medicinal Plants, ACECR, 2023)
Background: Solanum cernuum Vell. (Solanaceae) is a native plant from Brazil traditionally used for treating ulcers, liver damage, skin infections, gonorrhea, and benign prostatic hyperplasia (BPH). Objective: To evaluate the impact of hydroalcoholic extract and cernumidine obtained from S. cernuum Vell. leaves against prostate primary smooth muscle cell culture and assess their potential effect in inducing apoptosis (annexin V assay by flow cytometry). Methods: The hydroethanolic extract of S. cernuum was obtained by macerating powdered dried leaves followed by fractionation, furnishing 4.8 % w/w of cernumidine alkaloid as established by high performance liquid chromatographic analysis. Primary BPH smooth muscle cell culture was used in cell proliferation and apoptosis assays, whereby prostate smooth muscle cells were subjected to 0.125-5.0 mg/mL of hydroethanolic extract and 0.025-1.0 mg/mL of cernumidine for 48, 72, and 96 h. Results: Hydroethanolic extract (2 mg/mL) and cernumidine (1 mg/mL [3.3 × 10-6 M]) inhibited the cell growth by 60 % and 62 % at 96 h, respectively, and eventually led to cell death by apoptosis. On the other hand, only cernumidine (1 mg/mL) induced significant death by necrosis compared to control. Conclusion: The obtained findings corroborate the use of S. cernuum in native medicine and indicate that cernumidine is a promising candidate for further studies focusing on BPH treatment.